2012
DOI: 10.6002/ect.2011.0136
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sex on Biomechanical Properties of the Proper Hepatic Artery in Pigs and Humans for Liver Xenotransplant

Abstract: Objectives: This study investigated the relation between biomechanical properties of the proper hepatic artery and sex in pigs and humans to provide the theoretical basis for selecting suitable donor in pig-to-human liver xenotransplant. Materials and Methods:The proper hepatic arteries of 32 Chinese Hubei white pigs (8 males, 8 females, 8 castrated males, and 8 ovariectomized females) and 10 deceased donors (5 human men, 5 human women) were obtained. The pressure-diameter relations of the proper hepatic arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…As a comparison, heptocellular carcinoma tumors were reported to have a range of 20.4-75 kPa, and metastatic liver tumors may have a range of 23.6-75 kPa (Masuzaki et al, 2007). Likewise, normal liver tissue ranges from $15 kPa to $1 MPa depending on the applied strain (Rosen et al, 2008;Umale et al, 2013) while the elasticity of the hepatic veins and arteries is $30 kPa at normal blood pressure (Wang et al, 2009a;Li et al, 2012). We did not extend the modulus beyond 250 kPa as our earlier study showed that the therapy became independent of stiffness at higher stiffness values (Xu and Bigelow, 2011).…”
Section: Measurement Of Mechanical Properties Of Agarmentioning
confidence: 99%
“…As a comparison, heptocellular carcinoma tumors were reported to have a range of 20.4-75 kPa, and metastatic liver tumors may have a range of 23.6-75 kPa (Masuzaki et al, 2007). Likewise, normal liver tissue ranges from $15 kPa to $1 MPa depending on the applied strain (Rosen et al, 2008;Umale et al, 2013) while the elasticity of the hepatic veins and arteries is $30 kPa at normal blood pressure (Wang et al, 2009a;Li et al, 2012). We did not extend the modulus beyond 250 kPa as our earlier study showed that the therapy became independent of stiffness at higher stiffness values (Xu and Bigelow, 2011).…”
Section: Measurement Of Mechanical Properties Of Agarmentioning
confidence: 99%